PENGARUH PREVENTIVE MAINTENANCE COST DAN BREAKDOWN MAINTENANCE COST TERHADAP JUMLAH PRODUKSI (Studi Kasus pada Home Industry Sandal Corlis Mangkubumi Kota Tasikmalaya) - Risa Destia (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2022)
The purpose of this study was to determine and analyze Preventive Maintenance Costs, Breakdown Maintenance Cost, and Production Quantity at Home Industry Sandal Corlis Mangkubumi Tasikmalaya; Effect of Preventive Maintenance Cost and Breakdown Maintenance Cost simultaneously affect the quantity of production at Home Industry Sandal Corlis Mangkubumi Tasikmalaya; Effect of Preventive Maintenance Cost and Breakdown Maintenance Cost partially affect the quantity of production at Home Industry Sandal Corlis Mangkubumi Tasikmalaya. The research method used is a case study method with a quantitative approach. The analysis tool uses multiple linear regression. The data used is primary data. Based on the research results, it is known that Preventive Maintenance Costs and Breakdown Maintenance Costs simultaneously have a significant affect the quantity of production of Home Industry production of Sandal Corlis Mangkubumi, Tasikmalaya, Preventive Maintenance Costs partially have a significant effect on the quantity of production, Breakdown Maintenance Costs partially have a significant effect on the quantity of production